Neurocognitive Predictors of Treatment Outcomes in Cognitive Processing Therapy for Post-traumatic Stress Disorder: Study Protocol - Cenkner, David P.; Asnaani, Anu; DiChiara, Christina; Harb, Gerlinde C.; Lynch, Kevin G.; Greene, Jennifer; Scott, J. Cobb (Frontiers in Psychology, 2021)
Background: Posttraumatic stress disorder (PTSD) is a prevalent, debilitating, and costly psychiatric disorder. Evidenced-based psychotherapies, including Cognitive Processing Therapy (CPT), are effective in treating PTSD, although a fair proportion of individuals show limited benefit from such treatments. CPT requires cognitive demands such as encoding, recalling, and implementing new information, resulting in behavioral change that may improve PTSD symptoms. Individuals with PTSD show worse cognitive functioning than those without PTSD, particularly in acquisition of verbal memory. Therefore, memory dysfunction may limit treatment gains in CPT in some individuals with PTSD. Methods and Analysis: Here, we present a protocol describing the Cognition and PsychoTherapy in PTSD (CPTPTSD) study, a prospective, observational study examining how cognitive functioning affects treatment response in CPT for PTSD (NCT# 03641924). The study aims to recruit 105 outpatient veterans with PTSD between the ages of 18-70 years. Prior to beginning 12 sessions of CPT, Veteran participants will have standardized assessments of mood and functioning and complete a comprehensive neurocognitive battery assessing episodic learning, attention and speed of processing, language ability, executive control, and emotional functioning. This study aims to fill gaps in the current literature by: 1) examining the specificity of memory effects on treatment response; 2) exploring how baseline cognitive functioning impacts functional outcomes; and 3) examining potential mechanisms, such as memory for treatment content, that might explain the effects of baseline memory functioning on PTSD symptom trajectory. Discussion: If successful, this research could identify clinically relevant neurocognitive mechanisms that may impact PTSD psychotherapy and guide the development of individualized treatments for PTSD.